2007
DOI: 10.1021/ma070071j
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of a Nickel Diimine in Ethylene Polymerization with Immobilized Fe-, Cr-, and Ti-Based Catalysts on MgCl2 Supports

Abstract: Significant increases in the productivity of iron-, chromium-, and titanium-based MgCl2-supported catalysts for ethylene polymerization have been obtained by incorporation of a limited amount of a nickel diimine catalyst giving branched polyethylene. Formation of the latter during the early stages of polymerization reduces the monomer diffusion limitation inherent in ethylene homopolymerization, thereby increasing the productivity of the main catalyst component. The final products are essentially linear, high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…These catalysts are well known for production of respectively branched and linear polyethylene chains depending on the applied reaction conditions [34][35][36][37]. Both catalysts were supported on the TIBA-modified MgCl 2-nEtOH adduct, separately and concurrently, at different ratios.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…These catalysts are well known for production of respectively branched and linear polyethylene chains depending on the applied reaction conditions [34][35][36][37]. Both catalysts were supported on the TIBA-modified MgCl 2-nEtOH adduct, separately and concurrently, at different ratios.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Chadwick et al have discovered that Cp 2 TiCl 2 and other titanium-based single-site catalysts can be readily immobilized and activated on these supports, without the use of MAO or borate activators [36]. They have shown that through this method, a-diimine nickel catalysts could also be activated with traditional TEA activator, but immobilization may suppress chain walking and end in higher population of shorter methyl branches [42].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to other polystyrene [138] and silica supports [139,140,141,142,143,144] , iron and cobalt precatalysts have been immobilised on calcosilicate [145] , magnesium dichloride [146,147,148,149] , MCM-41 zeolite [150,151] , clay [152] and fluorotetrasilicic mica [153] . Supported systems have also been examined using alternative activators [154,155,156,157,158,159] .…”
Section: Supported Catalystsmentioning
confidence: 99%